21st Century Conscientization: Critical Pedagogy and the Development of Competitive Capacity in Colombian Corteros - Angela Barrios; Carmela Nanton MS (Adult Education Research Conference, 2008)
The Colombian sugarcane industry presents a unique 21st century opportunity to analytically examine an emergent Human Resource Development (HRD) problem of the “corteros”, key stakeholders of this lucrative industry. Critical pedagogy, competitive capacity, and conscientization theoretically frame the discussion, solution, and implications of the relationship between Adult education and HRD.
Keywords: competitive capacity; conscientization; critical pedagogy; HRD